Dependence of the effect of pressure on the bearing surface on the pressure in a summer tire of size 225/55 R18 - Pysartsov, O.; Писарцов, Олександр Сергійович (Харківський національний автомобільно-дорожній університет, 2025)
During the study of the influence of tire pressure on the bearing surface of M1 category vehicles, it was found that research on modern tire sizes has not been conducted. This can be useful when driving general traffic vehicles on the rough terrain. This served as the motivation for the present study. This article investigates the relationship between internal tire pressure and the pressure exerted by the vehicle on the bearing surface. The issue of optimizing tire pressure is especially relevant for ensuring high passability, reducing stress on road surfaces, and improving handling, especially under operating conditions on soft or uneven terrains such as sand, mud, or snow. Options for influencing the pressure on the supporting surface to increase the cross-country ability of the vehicle and practical solutions for increasing the passability are also considered. The purpose of the study was to determine the relationship between changes in internal tire pressure and the specific pressure exerted on the bearing surface. Originality. An experimental study was carried out according to the algorithm presented in the article on a vehicle of category M1 of general cross-country ability "Opel Grandland 1.5 BHDi" at the level of a concrete surface with Michelin Primacy 3 summer tires of size 225/55 R18 98V installed. Results. It was determined that reducing the tire pressure from 2.1 to 1.6 atmospheres leads to a decrease in bearing surface pressure from 1.37 to 1.08 kg/cm², which potentially improves vehicle passability. The mechanism of influence of car weight and tire contact area with the supporting surface from the pressure value in summer tires of standard size 225/55 R18 is described. An almost inverse proportional relationship between tire pressure and bearing surface pressure was also established. The article presents graphical and analytical dependencies and substantiates the feasibility of reducing tire pressure in the context of vehicle operation under challenging road conditions. Practical value. The results of the study can be applied in the design of wheeled vehicles, as well as in the practical operation of vehicles in off-road conditions.
Залежність впливу тиску на опорну поверхню від тиску в літній шині розміром 225/55 R18
Keywords: tire pressure; bearing surface pressure; contact patch area; passability; tires; Opel Grandland; тиск у шині; тиск на опорну поверхню; площа плями контакту; прохідність; шини; 629.01; 10.30977/AT.2219-8342.2025.56.0.02